Performance of carbide and ceramic tools in the milling of compact graphite iron - CGI - Gabaldo S. (2010)
Grey cast iron (GCI) is the most common material used in diesel engine blocks. However, to increase the pressures in the combustion chamber when this kind of alloy is used, it is necessary to increase the block wall thickness, what raises its weight and, consequently, does not fulfill the requirements. Thus, the compacted graphite iron (CGI) appears as an alternative for such application. It has characteristics of heat conductivity and damping similar to the GCI, but with superior mechanical properties, making possible the manufacturing of lighter engines with better performance. However, the use of CGI presents as disadvantage its worse machinability, when compared with GCI, stimulating development of machining techniques and cutting tool materials. The goal of this work is to analyze the performance of two tool materials (carbide and ceramic Si3N4) in the finishing milling of the fire face of the engine block made of CGI. To reach this goal these two materials were compared in terms of wear mechanisms and tool life in different cutting speeds. The main conclusion was that, for conditions similar to those used in this work, carbide is better than ceramic in terms of tool life in the milling CGI. Copyright © 2010 by ABCM.